THE ROLE OF INTERCULTURAL COMMUNICATION COMPETENCE IN FOREIGN LANGUAGE TEACHING: CHALLENGES AND OPPORTUNITIES IN UZBEKISTAN - Muxtarov Abduvali; To`raxon Abdurahmonov (TADQIQOTLAR, 2026)
Introduction In today’s globalized world, the ability to communicate effectively across cultural boundaries has become an essential skill. Foreign language education is no longer limited to mastering grammar and vocabulary; it increasingly encompasses the development of intercultural communication competence (ICC). ICC refers to the ability to interact appropriately and effectively with individuals from diverse cultural backgrounds. This competence enables language learners to navigate cultural nuances, avoid misunderstandings, and engage in meaningful communication in real-life contexts. The Republic of Uzbekistan, amid its rapid integration into the global community, has recognized the importance of ICC in foreign language teaching. Recent curriculum reforms emphasize national and global cultural competencies as critical outcomes for students. However, challenges remain in teacher training, curriculum design, and resource availability, which hinder the full integration of ICC into language education. This thesis explores the role of intercultural communication competence in foreign language teaching, examines current pedagogical approaches, and discusses the practical challenges and opportunities related to its implementation in Uzbekistan’s educational context.